2017
DOI: 10.9745/ghsp-d-16-00311
|View full text |Cite
|
Sign up to set email alerts
|

Limited Service Availability, Readiness, and Use of Facility-Based Delivery Care in Haiti: A Study Linking Health Facility Data and Population Data

Abstract: Proximity to a health facility offering delivery services and readiness of the facilities to provide such services were poor in both rural and urban areas outside of Port-au-Prince. Availability of a proximate facility was significantly associated with women in rural and urban areas delivering at a facility, as was the quality of delivery care available at the facilities but only in urban areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 29 publications
11
58
0
Order By: Relevance
“…Information from Malaria Indicator Surveys and of the Health Management Information System can be included as additional components of this index to look into other aspects of case management, such as delays of seeking care, the severity of cases consulting or the quality of care provided. Our results corroborate with previous investigations done in Ghana, Mozambique, Tanzania, Nigeria, Bangladesh and Haiti that also used SARA or similar survey data and revealed a positive effect of readiness on health outcome[15][16][17][18]24,25].The lack of a statistically important association between facility readiness and malaria mortality in medical centres might be explained by the severity of malaria cases seeking treatment in medical centres. Indeed, peripheral health centres refer complicated cases to medical centres.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Information from Malaria Indicator Surveys and of the Health Management Information System can be included as additional components of this index to look into other aspects of case management, such as delays of seeking care, the severity of cases consulting or the quality of care provided. Our results corroborate with previous investigations done in Ghana, Mozambique, Tanzania, Nigeria, Bangladesh and Haiti that also used SARA or similar survey data and revealed a positive effect of readiness on health outcome[15][16][17][18]24,25].The lack of a statistically important association between facility readiness and malaria mortality in medical centres might be explained by the severity of malaria cases seeking treatment in medical centres. Indeed, peripheral health centres refer complicated cases to medical centres.…”
supporting
confidence: 91%
“…The index was utilized to assess the association between facility readiness with child survival, low birth weight, maternal and neonatal death in Ghana [15]. PCA has been applied to relate general service readiness and health financing factors in 10 countries in Africa and Asia [16], health facility readiness to pregnancy delivery services and service utilization in Haiti [17] or to assess facility readiness to maternal health services over time in Nigeria [18]. Of note, Ssempiira et al (2019) criticized the use of PCA on binary items and derived a readiness index based on multiple correspondence analysis (MCA) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used a more nuanced service quality score based on a variety of measures of facility, provider, and service availability 7,8,38 but relied on measurement at a single point in time. Exploring methods to combine the richness of facility survey data with the timeliness of supply logistics data may eliminate the tradeoff between breadth and depth, providing a fruitful avenue for further study.…”
Section: Discussionmentioning
confidence: 99%
“…Lower level facilities in Haiti have been found to be poorly equipped to provide obstetric care even if they do provide labor and delivery services. [25] We also found that the risk of dying was highest among babies admitted at birth fromindicating that the sickest babies were also those who were transferred right at birth from HIC as opposed to babies born elsewhere who likely died before being brought in, contributing to potential selection bias in our sample. We did not record length of stay in hours and it is possible that babies admitted from HIC were merely alive for a few hours before succumbing to their illnesses.…”
Section: Discussionmentioning
confidence: 71%